(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The purpose of this paper isto evaluate the applicability of functional requirements developed on the practices of records management system in the Malaysian Court of Appeal.A single case study approach was selected in this study. The instruments used for data collection are; (i) online focus group discussion by giving the international experts in Electronic Records Management (ERM) to review the functional requirements, (ii) face to face interviews with IT personnel of the Malaysian Court of Appeal and (iii) face to face focus group discussion with the members of International Research on Permanent Authentic Records in Electronic Systems Project (InterPARES).The finding reveals that, the functional requirement that was developed, in line with the Malaysian Court of Appeal’s ERM practice. Thus, it is hoped that the documented functional requirements could encourage the majority of the courts in Malaysia to have standardized ERM requirements and improving data sharing with other courts and judicial agencies. Besides, the functional requirements developed are not only meant to assist in designing related system, but also to assess the capability of software packages that is currently in place. The functional requirements could also be used toassist in streamlining the management of court records, save file storage space, reduce manual handling of files and contribute to the preservation of corporate memory.